Balancing Agile Combat Support Manpower to Better Meet the Future Security Environment - Mills, Patrick (RAND Corporation, 2014)
This report proposes new metrics to measure expeditionary agile combat support (ACS) capacity and uses these metrics to assess the capacity of the current ACS manpower mix to support expeditionary operations, finding that there are imbalances among its career fields relative to expeditionary demands. This report develops and assesses several rebalanced manpower mixes to address these imbalances.